Thermal properties of wood flour reinforced polyamide 6 biocomposites by twin screw extrusion - Abdullah, Norihan; Abdan, Khalina; Lee, Ching Hao; Mohd Roslim, Muhammad Huzaifah; Radzuan, Mohd Nazren; Shafi, Ayu Rafiqah (De Gruyter, 2022)
The use of waste wood flour as polymer reinforcements has recently gained popularity because of its environmental benefits. The goal of this research is to determine the thermal properties of a waste wood flour/polyamide 6 composite made via extrusion. The fillers were melt compounded with polyamide 6 at filler concentrations of 5%, 10%, and 15% using a twin screw extruder, followed by compression molding. The processability of waste wood flour/polyamide 6 composite was evaluated using thermogravimetric analysis (TGA), differential scanning calorimeter (DSC), and dynamic thermomechanical analysis (DMA). According to the TGA analysis, the thermal stability of the composites decreases as the natural fiber content increases. The onset temperature of rapid thermal deterioration was reduced somewhat from 425 °C (neat PA6) to 405 °C (15 wt% wood flour). According to the DSC results, the addition of natural fibers resulted in quantify changes in the glass transition (Tg), melting (Tm), and crystallization temperature (Tc) of the PA6 composites. The storage modulus from the DMA study increased from 1177 MPa (neat PA6) to 1531 MPa due to the reinforcing effects of wood flour (15 wt%). Waste wood flour/polyamide 6 composites offer advantageous thermal properties, enabling us to profit from the strengthening potential of such cellulosic reinforcements while remaining recyclable and generally renewable.